HUBUNGAN PERSONAL HYGIENE DENGAN KEJADIAN DERMATITIS KONTAK IRITAN PADA PEKERJA DI PT.PERINDUSTRIAN DAN PERDAGANGAN BANGKINANG TAHUN 2016 - MILDA HASTUTY (Universitas Pahlawan Tuanku Tambusai, 2018)
Research surveillance in the United States states that 80% of occupational dermatitis is irritant contact dermatitis characterized by the presence of erythema (redness), edema (swelling) mild and cracked after the exposure of contents material from outside.Research to know the relationship of personal hygiene with incidence of disease skin (irritant contact dermatitis) to workers in PT. Industry and Trade Bangkinang in 2016. Cross Sectional research design, this research was conducted in Desember 2016 at PT. Industry and Trade Bangkinang.Sampel in this study are workers in PT. Industry and Trade Bangkinang numbering 92 people. Sample technique used Simple Random Sampling .. The data obtained were analyzed by chi square test. The results showed there was a personal hygiene relationship with irritant contact dermatitis on workers obtained p value = 0,036. For PT. Industry and Trade Bangkinang is expected to be a reference especially in designing rules, and policies for workers to prevent the occurrence of skin diseases (irritant contact dermatitis) by improving good personal hygiene and achieving a healthy work environment for its workers.